Assessment of Duplex PCR for the simultaneous diagnose of Mycobacterium spp. and Brucella spp. in cattle - Escobar, Ariel (2013)
Tuberculosis and brucellosis remain important causes of morbidity and mortality in many countries, for the detection of both diseases requires efficient and sensitive tool for effectuate the diagnosis. This study was aimed to evaluate and compare the duplex PCR versus the nested PCR, for detection of Brucella spp. (BR) and Mycobacterium spp. (TB). A total of 100 samples of tissues from tracheo-bronchial lymph nodes, bovine lung and bacterial isolate as positive controls were used. Were evaluated ten combinations of primers which were designed to flank the segment of the 16S rRNA sequence (RB) and antigen gen MPB70 (TB), the best result for the Duplex PCR was obtained with the primers Bru-2F/Bru-2R for BR and Tub-1F/Tub-N-R for TB. The amplification of the products was 225 and 230-bp respectively. In order to compare the results of the proposed technique, all samples were initially analyzed and compared between PCR and nested PCR (Kappa, k = 0.85) and the concordance between Duplex PCR and nested PCR (k = 0.88) for the two bacteria was very good.